Uncertainties of room acoustics simulation due to directivity data of musical instruments - Accolti Mostazo, Ernesto Enrique (2023)
The directional index of sound sources such as musical instruments is an important input for the current methods of room acoustics simulations. In this article, the uncertainty of the directional factor of musical instruments for each band is analyzed. First, the directional factors in third octave bands are estimated from a dataset of measurements obtained with a microphones array [S. Weinzierl et al., A Dataset of Anechoic Microphone Array Measurements of Musical Instruments, DepositOnce Repository, 2017]. Then, different methods to estimate the directional factor in third octave bands are analyzed, of which the method of averaging directional indices is selected due to its lower uncertainty and main error. Finally, the uncertainty propagation due to the selected method is studied based on predictions of time varying sound pressure level and dynamic loudness in a concert hall simulated by geometrical acoustics (GA) methods. About 50000 tones are simulated and its time varying sound level and loudness are calculated in order to evaluate its uncertainty at the audience due to the uncertainty on the input parameter source direcivity. The effects of source and receiver positions and instruments are shown through probability density function estimations of the sound level differences and excess loudness ratios between usual and control situations. About 50% of the studied data shows sound level differences close to 5dB and loudness excess ratio close to about 35%.